Viewpoint: The Physics in the New Era of Computing - Kamberaj, Hiqmet (European Scientific Journal, ESJ, 2023)
The 21st century is the Information Age, characterised by an economy based on information computerisation. In this new era of computing, the role of physics is becoming crucial and practical. Thus, physics is not seen anymore as an abstract and purely academic endeavour. This study addresses physics inventions’ contributions to computer science, society, and the economy. In particular, the physics discoveries in superconductivity, quantum mechanics, elementary particle physics, vacuum tubes, transistors and integrated circuits, electronic digital computer, fibre optics, lasers, and quantum computers will be discussed.